STUDENTS' MISCONCEPTIONS IN SOLVING STORY PROBLEMS OF TWO-VARIABLE LINEAR EQUATION SYSTEMS ASSESSED FROM NUMERACY LITERACY - Anugerah Kurniawati; Zubaidah R; Hamdani (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
Misconceptions in solving story problems involving the System of Linear Equations of Two Variables (SPLDV) are often a challenge for students. This research aims to identify the types of misconceptions experienced by students of grade VIII of Kasih Yobel Junior High School in Singkawang in solving SPLDV story problems, which are studied from the perspective of numeracy literacy. This research used descriptive qualitative method involving six students as research subjects. Data were collected through diagnostic tests and interviews to identify misconceptions based on numeracy literacy components: understanding, use, interpretation, and communication. The results showed that students experienced several types of misconceptions, especially in the translation of story problems into mathematical form, the use of strategies/methods, and calculations. The misconceptions were caused by students' lack of understanding of the basic concepts of SPLDV and inability to apply mathematical symbols and operations correctly. The discussion of the research results emphasizes the importance of learning approaches that strengthen students' numeracy literacy, especially in terms of understanding concepts and applying effective strategies. The conclusion of this study shows that improving numeracy literacy needs to be a priority in mathematics teaching to reduce misconceptions and improve students' ability to solve SPLDV story problems.